Impact of the morphological properties of thin TiO2 photocatalytic films on the detoxification of water contaminated with the cyanotoxin, microcystin-lr - Antoniou, Maria G.; Nicolaou, Persoulla A.; Shoemaker, Jody A.; De La Cruz, Armah A.; Dionysiou, Dionysios Demetriou (My University, 2009)
This study investigated the use of thin transparent TiO2 photocatalytic films, prepared with novel sol-gel methods containing surfactants as templating materials, for the degradation of the cyanotoxin, microcystin-LR (MC-LR). MC-LR is an emerging contaminant from the Contaminant Candidate Lists (CCLs 1-3) of the USEPA. The effects of UV-A radiation, solution pH, initial toxin concentration, coated surface area of the TiO2 films and their structural properties (porosity, crystallinity and thickness) on the degradation rate of MC-LR were investigated. Photolysis did not occur with UV-A radiation. Acidic pH was more efficient for the degradation of MC-LR due to toxin interaction with the catalyst surface and increased adsorption into the porous films. The degradation profiles of the toxin at different initial concentrations were fitted with pseudo-first order kinetics. Films prepared with three coatings (0.3 μm thickness) had the best performance at acidic and neutral pH, while the exclusion of surfactant from the preparation method resulted in non-porous films with decreased performance. The parameter that mostly affected the degradation rate was the solution pH. The toxicity of the treated samples, evaluated by an in-house protein phosphatase 1 assay, indicated that treatment with the TiO2 photocatalytic films indeed resulted in complete removal of MC-LR's toxicity.
Keywords: Cyanotoxins; Microcystin-LR; Photocatalytic; TiO2 photocatalysis; Thin films; Water treatment; Water detoxification; PP1 enzyme